ANALISIS IMPLEMENTASI KEBIJAKAN PERCEPATAN PENCEGAHAN DAN PENANGGULANGAN STUNTING DAN IMPLIKASINYA BAGI KEMADIRIAN KESEHATAN DI KABUPATEN BONE BOLANGO - Lutfia Bakari; Yahya Antu; Andi Yusuf Katili (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze the policy to accelerate stunting prevention and control in Bone Bolango Regency and its implications for regional health independence in Gorontalo Province. The focus of this research is the implementation of policies to accelerate stunting prevention and the implications of policies on health independence. The population is determined by purposive sampling and purposive sampling. The data analysis used is a qualitative descriptive method, namely identifying related to the implementation of policies to accelerate stunting prevention and the implications of policies for health independence. In general, the implementation of stunting prevention social policies in Bone Bolango Regency has been going well. The stunting prevention and control policy emphasizes aspects of commitment and responsibility of local governments and community participation as the main issues. The Bone Bolango district government is expected to maintain its commitment to overcome stunting problems by improving coordination in all regional apparatuses related to stunting. Public education is needed about the importance of eating nutritious foods with a balanced nutritional pattern. Improvement from the downstream side, namely by increasing agricultural production through intensification and extensification of agricultural cultivation, as well as providing decent jobs for the community, so as to increase people's purchasing power.